Detecting imported malaria infections in endemic settings using molecular surveillance: current state and challenges - Safarpour, Mahdi; Cabrera-Sosa, Luis; Gamboa, Dionicia; Van geertruyden, Jean-Pierre; Delgado-Ratto, Christopher (Frontiers in Epidemiology, 2025)
The Global Technical Strategy for Malaria 2016–2030 targets eliminating malaria from at least 35 countries and reducing case incidence by 90% globally. The importation of parasites due to human mobilization poses a significant obstacle to achieve malaria elimination as it can undermine the effectiveness of local interventions. Gaining a comprehensive understanding of parasite importation is essential to support control efforts and advance progress toward elimination. Parasite genetic data is widely used to investigate the spatial and temporal dynamics of imported infections. In this context, this systematic review aimed to aggregate evidence on the application of parasite genetic data for mapping imported malaria and the analytical methods used to analyze it. We discuss the advantages and limitations of the genetic approaches employed and propose a suitable type of genetic data along with an analytical framework to discriminate imported malaria infections from local infections. The findings offer potential actionable insights for national control programs, enabling them select the most effective methods for detecting imported cases. This also may aid in the evaluation and refinement of elimination programs by identifying high-risk areas and enabling the targeted allocation of resources to these regions.